2011
DOI: 10.1007/s11130-011-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant and Cytotoxic Activities of the Carob Tree (Ceratonia siliqua L.) Germ Flour Extracts

Abstract: This work aimed to evaluate the phytochemical content and to determine the antioxidant and cytotoxic activities of methanol extracts of the carob tree (Ceratonia siliqua L.) germ flour. The extracts were rich in phenolic compounds, had considerable antioxidant activity, and reduced the viability of cervical (HeLa) cancer cells. The chemical content and the biological activities of the extracts were significantly affected by gender and cultivar. Female cultivar Galhosa had the highest levels of phenolic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 26 publications
8
38
1
1
Order By: Relevance
“…siliqua (CS) was one of the most effective extracts in the antioxidant assays performed herein and its coffee extract also exhibited a moderate level of inhibition against the enzymes tested. Although there has been no report on cholinesterase inhibitory activity of this plant so far, several studies (Custódio et al, 2011;Kumazawa et al, 2002) have described a remarkable antioxidant effect of different parts of CS, which is in accordance with our data.…”
Section: Discussionsupporting
confidence: 92%
“…siliqua (CS) was one of the most effective extracts in the antioxidant assays performed herein and its coffee extract also exhibited a moderate level of inhibition against the enzymes tested. Although there has been no report on cholinesterase inhibitory activity of this plant so far, several studies (Custódio et al, 2011;Kumazawa et al, 2002) have described a remarkable antioxidant effect of different parts of CS, which is in accordance with our data.…”
Section: Discussionsupporting
confidence: 92%
“…The use of several methodologies of extraction and different solvents (Korukluoglu, Sahan, Yigit, Tumay Ozer, & Gucer, 2010), the sample origin (Hayes, Allen, Brunton, O'Grady, & Kerry, 2011), and its genetic (Custódio et al, 2011b) contribute to the differences observed in phenolic profile by HPLC test from study to another (Roseiro et al, 2013;Rtibi et al, 2017).…”
Section: Glycation Reaction Induces Modifications Of Protein Second-mentioning
confidence: 99%
“…Nowadays, carob seeds have been paid attention on and they have acted an important role economically since they are used as food additives, in pharmaceutical and cosmetic industries. [5][6][7] In vitro antioxidant activities of CP have been examined by Fe +3 reducing, radical scavenging power activity 8 and by oxidation of linoleic acid. 9 Carob seeds are a particularly rich source of complex polymers of flavonoids such as proanthocyanidin, ellagitannin, and gallotannin.…”
Section: Introductionmentioning
confidence: 99%